Elaboración y fabricación de cinco de los personajes alternos de las festividades de las octavas del corpus christi del cantón Pujilí, para dar a conocer a la colectividad la importancia de los mismos - Loján Jácome, María Isabel (2016)
This project has as objective stands out and reassess for five of the alternate characters from Octavas del Corpus Christi, Pujili canton, that make each year in the second week of June, the reason to this celebration is to give to thank bythe good harvest obtained in the course of the year, the danzante is the main representative icon this cult in honor to the corn´s harvest. According to the research carried out it necessary the development of the same, because don´t pay attention to these characters and with the passing of the years, they are being forgotten, this problem had found in 90% of the Pujilence population that unknown the function that do each one of them, for that reason the development of this work is encouraged to make to give relevance to the characters through the artisan manufacture with the use of the mud (material used by all craftsmen of the town), this work will permit to create awareness in the society.